Targeted proteomics reveals quantitative differences in low-abundance glycosyltransferases of patients with congenital disorders of glycosylation - Sakson, Roman; Beedgen, Lars; Bernhard, Patrick; Alp, K. Merve; Lübbehusen, Nicole; Röth, Ralph; Niesler, Beate; Luzarowski, Marcin; Shevchuk, Olga; Mayer, Matthias P.; Thiel, Christian; Ruppert, Thomas (International journal of molecular sciences, 2024)
Protein glycosylation is an essential post-translational modification in all domains of life. Its impairment in humans can result in severe diseases named congenital disorders of glycosylation (CDGs). Most of the glycosyltransferases (GTs) responsible for proper glycosylation are polytopic membrane proteins that represent challenging targets in proteomics. We established a multiple reaction monitoring (MRM) assay to comprehensively quantify GTs involved in the processes of N-glycosylation and O- and C-mannosylation in the endoplasmic reticulum. High robustness was achieved by using an enriched membrane protein fraction of isotopically labeled HEK 293T cells as an internal protein standard. The analysis of primary skin fibroblasts from eight CDG type I patients with impaired ALG1, ALG2, and ALG11 genes, respectively, revealed a substantial reduction in the corresponding protein levels. The abundance of the other GTs, however, remained unchanged at the transcript and protein levels, indicating that there is no fail-safe mechanism for the early steps of glycosylation in the endoplasmic reticulum. The established MRM assay was shared with the scientific community via the commonly used open source Skyline software environment, including Skyline Batch for automated data analysis. We demonstrate that another research group could easily reproduce all analysis steps, even while using different LC-MS hardware.
Gesehen am 26.11.2024